Investigation on the Causes of Delay in Construction Projects - Makram Riad, Karim Medhat (Universiti Teknologi PETRONAS, 2011)
Construction management in general & construction time in particular are part of important aspects that are required in the industry of construction projects. The importance of management is to ensure that all the planning is well executed to complete the project. The importance of construction time lies in in managing the activities of the project, so that it won't be delayed after the deadline. Delays are crucial industry breakers as they can have effects on money and resources. This research is focusing on identifying some factors that contribute to delay and their effects on construction projects. To be specific, the case study is focusing on the delay factors and effects in "The Proposed Design Construction And Completion Of 3 Star Hotel And Office Tower On Plot ZlO, Precint 1, Wilayah Persekutuan Putrajaya, Malaysia" project and "The New Petrojet Head Quarters, go•h Street, Fifth Avenue, cairo, Egypt." project. The methodology of the research is to select and identifY the projects, site observation, data collection, structured interview with the staff and in the end analyzing the data from the respective interviews using the average index calculation. The result of this research found that there are 9 main groups of factors that contribute to delay in both projects such as changes and variations, contractual relationships, political issues and many more. The factors were analyzed and discussed and the discussion led to the exploration of the delay effects in both projects. At the end of the research, several recommendations have been proposed to make future researches on this subject more viable and accurate.